Design, Synthesis, and Biological Evaluation of Novel Thienopyrimidine Derivatives as PI3Kα Inhibitors - Lide Yu; Qinqin Wang; Caolin Wang; Binliang Zhang; Zunhua Yang; Yuanying Fang; Wufu Zhu; Pengwu Zheng (Molecules, 2019)
Three series of novel thienopyrimidine derivatives 9a−l, 15a−l, and 18a−h were designed and synthesized, and their IC50 values against four cancer cell lines HepG-2, A549, PC-3, and MCF-7 were evaluated. Most compounds show moderate cytotoxicity against the tested cancer cell lines. The most promising compound 9a showed moderate activity with IC50 values of 12.32 ± 0.96, 11.30 ± 1.19, 14.69 ± 1.32, and 9.80 ± 0.93 µM, respectively. The inhibitory activities of compounds 9a and 15a against PI3Kα and mTOR kinase were further evaluated. Compound 9a exhibited PI3Kα kinase inhibitory activity with IC50 of 9.47 ± 0.63 µM. In addition, docking studies of compounds 9a and 15a were also investigated.